Tingkat Kelangsunganhidup (Survival Rate) Benih Ikan Koi (Cyprinus rubrofuscus) pada Air Hujan - Dini Sugihartini; Ujang Dindin; Novita MZ (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study was conducted to analyze the effect of rainwater on the survival of koi fry. The background of this study is based on the increasing demand for koi fish which encourages breeders to improve the quality and quantity of fry production. However, the success of seeding is influenced by several factors, especially air quality such as temperature and pH. Rainwater is known to have less stable quality, especially due to its low pH value, so it is necessary to study its impact on koi fry. This study was conducted on November 25–28, 2024 in the Bossbaster experimental pond, Legok Nyenang Village, Kadudampit District, Sukabumi Regency. The media used were 15 plastic gallons, each containing 5 liters of air and 40 newly hatched koi fry. The experimental design used a Completely Randomized Design (CRD) with 5 treatment levels and 3 replications. Treatments included A (100% rainwater), B (75% rainwater + 25% well water), C (50% rainwater + 50% well water), D (25% rainwater + 75% well water), and E (100% well water). The results of the ANOVA test showed that there was no significant difference (P>0.05) in the survival value of koi fish fry in the five treatments. Thus, it can be concluded that the use of rainwater does not have a significant effect on the survival of koi fish fry. In addition, the results of water quality observations showed that all parameters were still within the standard quality range, except for the temperature which was slightly below the standard.